Towards understanding cybersecurity capability in Australian healthcare organisations: a systematic review of recent trends, threats and mitigation. Issue 4 (6th June 2020) - Offner, K. L.; Sitnikova, E.; Joiner, K.; MacIntyre, C. R.
ABSTRACT: Cybersecurity threats in the Health sector are increasing globally due to the rising value of sensitive health information and availability of digitalised personal health records. This systematic review compares international and Australian health system cybersecurity landscapes in relation to the introduction of universal electronic health records. It examines recent trends in healthcare cybersecurity breaches that can disrupt essential services if patient safety and privacy are compromised. Often health systems and health mangers are ill-equipped to mitigate such threats. Recommendations are provided to proactively mature the cybersecurity culture within healthcare organisations, thus increasing their resilience to cyber threat.